Die Maatskappy vir Europese immigrasie : a study of the cultural assimilation and naturalisation of European immigrants to South Africa 1949 -1994 - Slater, Roland (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MA (History))--University of Stellenbosch, 2005.